2009
DOI: 10.1093/bja/aen403
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine has no effect on bispectral index during stable propofol–remifentanil anaesthesia

Abstract: Under stable propofol and remifentanil TCI anaesthesia, a slow bolus infusion of ketamine 0.2 mg kg(-1) administered over a 5 min period did not increase the BIS value over the next 15 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
(6 reference statements)
1
23
0
Order By: Relevance
“…In contrast, Vereecke et al [27] concluded that ketamine administration alone or with rocuronium could not affect BIS readings significantly so that the clinical setting should be considered during the interpretation of all indices. In addition, Faraoni et al [28] found that BIS values did not increase with ketamine in the absence of surgical stimulation. They removed the surgical pain effect on the EEG cortical measurements, which was reported to increase the BIS readings [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Vereecke et al [27] concluded that ketamine administration alone or with rocuronium could not affect BIS readings significantly so that the clinical setting should be considered during the interpretation of all indices. In addition, Faraoni et al [28] found that BIS values did not increase with ketamine in the absence of surgical stimulation. They removed the surgical pain effect on the EEG cortical measurements, which was reported to increase the BIS readings [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hans et al [13] concluded that a ketamine bolus of 0.5 mg/kg also significantly increases the BIS values, during a sevoflurane anaesthesia. Faraoni et al [12] showed that a ketamine bolus of 0.2 mg/kg administered over 5 min did not increase the BIS value over the next 15 min, during a propofol and remifentanil targetcontrolled infusion and Sengupta et al [11] verified, more recently, that a bolus dose of ketamine 0.2 mg/kg did not affect BIS values during propofol-fentanyl anaesthesia whereas a bolus dose of 0.5 mg/kg increased BIS values.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several authors have assessed the effect of different analgesic doses of ketamine in BIS values [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that TIVA with propofol and remifentanil do not affect BIS when infusing a low dose ketamine [27], while Hans et al [28] reported that anesthesia with sevoflurane increased BIS. In our study, BIS was higher in group K than C group, but both were within the range of general anesthesia.…”
Section: Discussionmentioning
confidence: 99%